Aproximación al análisis de la variación intra-locutor de las róticas en posición implosiva en tres géneros orales: Aspectos relevantes para la comparación forense de voces - Jordi Cicres; Núria Gavaldà (Del Español. Revista de Lengua, 2023)
Rhotic sounds have shown high variability in coda position in Peninsular Spanish (Blecua and Cicres, 2019) that could individualize voices in a forensic context (Blecua, Cicres and Gil, 2014). However, there is no evidence on the variation that these sounds may show within the same speaker depending on speech style. The present work studies the variation that rhotic sounds show in three recordings with different speaking styles produced by the same speaker, as well as the impact that the linguistic context —preconsonantal position and prepausal position— may have on this variation. The results indicate high intra-speaker variability in the number and acoustic characteristics of the components of these sounds in the three styles in preconsonantal position, although the characteristics of the components in preconsonantal position seem to be stable regardless of the speaking style.